1919 N.C. Sess. Laws 397, 397-399 - (:unkn) unknown (My University, 1919)
Pub. Laws, ch. 197, §§ 1-8: That it shall be unlawful for any person, firm, or corporation in this State to sell, give away or dispose of, or to purchase or receive, at any place within the State from any other place within or without the State, without a license or permit therefor shall have first been obtained by such purchaser or receiver from the clerk of the Superior Court of the county in which such purchase, sale, or transfer is intended to be made, any pistol, so-called pump-gun, bowie knife, dirk, dagger or metallic knucks.
Keywords: REGISTRATION; TRANSFER